The Implementation of Legal Protection for Child Perpetrators of Bullying (A Comparative Study of Indonesia and Finland) - Rasdi; Ika Anisatul Fatma Fitria (Law Research Review Quarterly, 2026)
Bullying involving children has become an increasingly serious issue in Indonesia and poses complex legal challenges, particularly when children are positioned not only as victims but also as perpetrators. The prevailing legal framework requires a careful balance between legal accountability and the protection of children’s rights. This article aims to analyze the implementation of legal protection for child perpetrators of bullying in Indonesia and to compare it with the juvenile justice approach applied in Finland. This research employs a normative legal research method using statutory, conceptual, and comparative approaches. The study examines legislation concerning child protection and the juvenile criminal justice system in Indonesia, relevant international legal instruments, as well as policies on bullying prevention and child protection in Finland. The findings indicate that, although Indonesian law normatively emphasizes the principle of child protection, including the application of diversion and restorative justice, its implementation in cases involving child perpetrators of bullying remains inconsistent and tends to be oriented toward punitive measures. In contrast, Finland prioritizes preventive efforts, psychosocial interventions, and school-based accountability mechanisms, thereby minimizing the use of criminal sanctions against children. This study concludes that enhancing the effectiveness of legal protection for child perpetrators of bullying in Indonesia requires strengthening restorative justice mechanisms, improving inter-agency coordination, and integrating prevention models that are non-punitive in orientation and centered on the best interests of the child.